Papers of E.W. Searle - Searle, E. W. (Edward William) 1887-1955. (1903)
References from various photographic firms who had employed Searle for various periods, and one letter from the staff of Hall and Co., photographers, to Searle on leaving the company. Also contains a view index of photographs taken during the 1940s and 1950s.
The Acc08/135 instalment includes Searle's personal diary 1939-1940; aerial photography journal; Cactus essay by Searle; comments on articles in The Australian surveyor; typed sheet on flying and photography; scrapbook of photographic articles; Along the Hawkesbury River of romance manuscript and two notebooks; descriptive articles on themes such as Sydney Harbour, Botany Bay, Mosman, Botanic Gardens, Hawkesbury River, and artists in the wilderness.
Manuscript reference no.: MS 1176, MS Acc08.135.
National Library of Australia Pictures collection.
National Library of Australia Map collection.
Photographer. E.W. Searle was a professional photographer associated with the firms Hall & Co. and Grace Bros. in Sydney. Searle also worked for J.W. Beattie in Hobart, 1911-1915.
Descriptive list available for Acc08/135 (draft).
Keywords: Searle, E. W. -- 1887-1955 -- Archives; Photographers -- Australia -- Archives; Photography -- Australia; Photographers